Capital Punishment and Lethal Acts in War - John Finnis (Studia Philosophiae Christianae)
In reply to the readily inferable denial, in para. 304 of the papal exhortation Amoris Laetitia, that there are any exceptionless negative moral norms, this article (1) recalls and reaffirms the philosophical and doctrinal tradition’s thesis that there are such norms. It then (2) sketches what is involved in identifying a kinds of act by its object; (3) reflects briefly on the three successive and different iterations of the teaching of the Catechism of the Catholic Church on capital punishment; and (4) draws attention to the Catechism’s notable but little discussed, non-pacifist teaching against all intending to kill, even in just war.